TECHNOLOGY OF CHEMICAL FIXATION OF ANCHOR FASTENERS USING ACRYLIC COMPOSITIONS - Zolotova, Nina; Suprun Оleh; Onyskiv, Anatoliy (Sworld-Us Conference proceedings, 2025)
This study is devoted to analysing the effectiveness of using acrylic compositions for anchor connections. The compositions under study, developed by specialists at the O.M. Beketov National University of Urban Economy in Kharkiv, demonstrate high perfor